Rút gọn rồi tính
√(6-√27)2 - √27
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =2/3-1/3=1/3
b: =3/5-1/7=21/35-5/35=16/35
c: =2/3-1/2=4/6-3/6=1/6
\(\dfrac{15}{35}+\dfrac{7}{10}=\dfrac{3}{7}+\dfrac{7}{10}=\dfrac{30}{70}+\dfrac{49}{70}=\dfrac{79}{70}\)
\(\dfrac{27}{72}+\dfrac{11}{24}=\dfrac{3}{8}+\dfrac{11}{24}=\dfrac{9}{24}+\dfrac{11}{24}=\dfrac{20}{24}=\dfrac{5}{6}\)
\(\dfrac{6}{12}+\dfrac{7}{6}=\dfrac{1}{2}+\dfrac{7}{6}=\dfrac{3}{6}+\dfrac{7}{6}=\dfrac{10}{6}=\dfrac{5}{3}\)
a: =8/5-2/3=24/15-10/15=14/15
12/20-6/18=3/5-1/3=9/15-5/15=4/15
b: 18/21-12/27=6/7-7/9=54/63-49/63=5/63
8/12-20/50=2/3-2/5=10/15-6/15=4/15
\(a,\dfrac{8}{5}-\dfrac{18}{27}=\dfrac{8}{5}-\dfrac{2}{3}=\dfrac{14}{15}\\ \dfrac{12}{20}-\dfrac{6}{18}=\dfrac{3}{5}-\dfrac{1}{3}=\dfrac{4}{15}\\ b,\dfrac{18}{21}-\dfrac{12}{27}=\dfrac{6}{7}-\dfrac{4}{9}=\dfrac{26}{63}\\ \dfrac{8}{12}-\dfrac{20}{50}=\dfrac{2}{3}-\dfrac{2}{5}=\dfrac{4}{15}\)
a: =1/4+1/4=2/4=1/2
b: =3/5+3/5=6/5
c: =5/9+7/9=12/9=4/3
a,\(\frac{4}{6}+\frac{18}{27}=\frac{2}{3}+\frac{2}{3}=\frac{4}{3}\)
b,\(\frac{15}{25}+\frac{6}{21}=\frac{3}{5}+\frac{2}{7}=\frac{21}{35}+\frac{10}{35}=\frac{31}{35}\)
a,4/6 = 2/3 ; 18/27 = 2/3
ta có: 2/3 + 2/3 = 4/3
b,15/25 = 3/5 ; 6/21 = 2/7
ta có: 3/5 + 2/7 = 6/2
\(\frac{3}{5}-\frac{5}{35}=\frac{21}{35}-\frac{5}{35}=\frac{16}{35}\)
\(\frac{18}{27}-\frac{2}{6}=\frac{1}{3}\)
\(\frac{15}{25}-\frac{3}{21}=\frac{16}{35}\)
\(\frac{24}{36}-\frac{6}{12}=\frac{1}{6}\)
tích đúng cho mk nhé
35−535=2135−535=163535−535=2135−535=1635
1827−26=131827−26=13
1525−321=16351525−321=1635
2436−612=16
6/18=1/3
6/24=1/4
1/3-1/4=4/12-3/12=1/12
18/27=2/3
5/15=1/3
2/3-1/3=1/3
\(\sqrt{\left(6-\sqrt{27}\right)^2}-\sqrt{27}=\sqrt{\left(3.\left(2-\sqrt{3}\right)\right)^2=3\sqrt{\left(2-\sqrt{3}\right)^2}}-3\sqrt{3}=3\left(2-\sqrt{3}\right)-3\sqrt{3}=6-3\sqrt{3}-3\sqrt{3}=6-6\sqrt{3}\)